Perbedaan Hasil Belajar Matematika Siswa yang Diajar Dengan Model Pembelajaran Think-Talk-Write Dan Missouri Mathematics Project - Akbar, Rahmat; Irvan, Irvan; Nasution, Marah Doly; Azis, Zainal (PHI: Jurnal Pendidikan Matematika, 2022)
The purpose of this research is to find out the difference in the mathematics learning outcomes of class VIII MTs Al-Washliyah Tanjung Mulia in the 2017/2018 school year on the tangent line to a circle. This research is a quasi-experimental type with a two group posttest only design. The research sample involved 26 students of class VIII-A who were given treatment with the TTW learning model, then 24 students of class VIII-B were given treatment with the MMP learning model. The sampling technique used is nonrandom. Research data were collected with several instruments, including interviews, questionnaires, and tests. The test instrument has gone through the validation stage by three validators, namely one mathematics teacher and two mathematics lecturers. The results of the final data test with t-test obtained tcount > ttable (846 > 1679). Based on these facts, it can be concluded that student learning outcomes using the MMP and TTW models at MTs Al-Wasliyah Tanjung Mulia in class VIII have significant differences.